Class Attitudes, Political Knowledge, and Support for Redistribution in an Era of Inequality. (10th January 2020) - Macdonald, David
Abstract : Objective: Why, despite positive feelings toward the poor and working classes, relative to the rich and big business, has American public support for redistribution failed to appreciably increase during an era of high, and rising, income inequality? Methods: I argue that this puzzling disconnect is due, in part, to a lack of general political knowledge. Using survey data from the 2012 American National Election Study, I test how political knowledge conditions the relationship between people's economic class group attitudes and their support for redistribution. Results: People with low (high) levels of political knowledge weakly (strongly) connect their class attitudes with support for redistributive spending and progressive taxation. Data from four ANES panel studies show that this does not result from the less knowledgeable holding weak "nonattitudes" toward these class groups. Rather, consistent with Converse's classic work, I attribute this to less knowledgeable individuals lacking awareness about how redistributive policies benefit different social groups. Conclusion: These findings help us to better understand an important puzzle in American politics: why a mass public that purports to favor the poor and working classes over the economic elite has not turned more strongly in favor of redistribution during an era of historic inequality.